2019
DOI: 10.1080/15592294.2019.1582276
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerobic exercise and fatty acid supplementation on global and gene-specific DNA methylation

Abstract: Lifestyle interventions, including exercise and dietary supplementation, can modify DNA methylation and exert health benefits; however, the underlying mechanisms are poorly understood. Here we investigated the impact of acute aerobic exercise and the supplementation of omega-3 polyunsaturated fatty acids (n-3 PUFA) and extra virgin olive oil (EVOO) on global and gene-specific (PPARGC1A, IL6 and TNF) DNA methylation, and DNMT mRNA expression in leukocytes of diseasefree individuals. Eight trained male cyclists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 88 publications
(126 reference statements)
3
45
0
Order By: Relevance
“…Few studies on EVOO and epigenetic modulation have been conducted. Recent papers have reported that EVOO supplementation can modulate DNA methylation in vivo [42], and downregulate HDAC2 and HDAC3; this second effect in particular might be exerted, as newly hypothesized, by a specific compound: oleuropein [43]. On the other hand, thymoquinone is probably the main compound responsible for modulation of gene expression observed in cells treated with NG oil.…”
Section: Discussionmentioning
confidence: 84%
“…Few studies on EVOO and epigenetic modulation have been conducted. Recent papers have reported that EVOO supplementation can modulate DNA methylation in vivo [42], and downregulate HDAC2 and HDAC3; this second effect in particular might be exerted, as newly hypothesized, by a specific compound: oleuropein [43]. On the other hand, thymoquinone is probably the main compound responsible for modulation of gene expression observed in cells treated with NG oil.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, EVOO‐containing diets decreased Dnmt3b expression in mammary tumours. Conversely, supplementation with EVOO has been shown to decrease DNMT1 expression in human peripheral blood leukocytes (Hunter et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These methylation changes were predominately in gene bodies and corresponded to changes in gene expression. A clinical intervention trial also demonstrated that supplementation for 8 days with n ‐3 PUFA (5.7 g·day −1 ) and EVOO (6 g·days −1 ) caused differential effects on the methylation of the gene encoding interleukin‐6 ( IL‐6 ) and expression of DNMT1 in circulating leukocytes (Hunter et al, ). Specifically, methylation of IL‐6 was increased following n ‐3 PUFA supplementation, whereas EVOO caused decreased methylation.…”
Section: Dietary Fat Obesity and Targeting Of Dna Methylation In Bcmentioning
confidence: 99%
“…Besides, several ‘anti-aging’ nutraceutical compounds have been recently proposed to counteract oxidative stress and senescence [ 40 ]. For example, both omega 3 polyunsaturated fatty acids (ω-3 PUFA) and extra virgin olive oil (EVOO) have been reported to exert numerous metabolic and cardiovascular benefits in the elderly due to their high content in antioxidant compounds [ 199 , 200 , 201 , 202 ]. In old rats, the treatment prevented aging-induced endothelial dysfunction, oxidative stress, inflammation, and vascular insulin resistance through activation of the PI3K/Akt pathway and decreasing the response to the vasoconstrictor angiotensin II [ 202 ].…”
Section: New Therapeutic Approaches Targeted Endothelial Dysfunctimentioning
confidence: 99%